Optimization of the diagnosis of inherited colorectal cancer using NGS and capture of exonic and intronic sequences of panel genes. (November 2018) - Baert-Desurmont, Stéphanie; Coutant, Sophie; Charbonnier, Françoise; Macquere, Pierre; Lecoquierre, François; Schwartz, Mathias; Blanluet, Maud; Vezain, Myriam; Lanos, Raphaël; Quenez, Olivier; Bou, Jacqueline; Bouvignies, Emilie; et al.
Abstract We have developed and validated for the diagnosis of inherited colorectal cancer (CRC) a massive parallel sequencing strategy based on: (i) fast capture of exonic and intronic sequences from ten genes involved in Mendelian forms of CRC (MLH1, MSH2, MSH6, PMS2, APC, MUTYH, STK11, SMAD4, BMPR1A andPTEN ); (ii) sequencing on MiSeq and NextSeq 500 Illumina platforms; (iii) a bioinformatic pipeline that includes BWA-Picard-GATK (Broad Institute) and CASAVA (Illumina) in parallel for mapping and variant calling, Alamut Batch (Interactive BioSoftware) for annotation, CANOES for CNV detection and finally, chimeric reads analysis for the detection of other types of structural variants (SVs). Analysis of 1644 new index cases allowed the identification of 323 patients with class 4 or 5 variants, corresponding to a 20% disease-causing variant detection rate. This rate reached 37% in patients with Lynch syndrome, suspected on the basis of tumour analyses. Thanks to this strategy, we detected overlapping phenotypes (e.g., MUTYH biallelic mutations mimicking Lynch syndrome), mosaic alterations and complex SVs such as a genomic deletion involving the lastBMPR1A exons andPTEN, anAlu insertion withinMSH2 exon 8 and a mosaic deletion ofSTK11 exons 3–10. This strategy allows, in a single step, detection of all types of CRC gene alterations including SVs and provides a high disease-causing variant detection rate, thus optimizing the diagnosis of inherited CRC.